Effect of Molar Ratio on Structural and Size of ZnO/C Nanocomposite Synthesized Using a Colloidal Method at Low Temperature - Siham Lhimr; Saidati Bouhlassa; Bouchaib Ammary (Universitas Gadjah Mada, 2019)
In this paper we study the effects of different molar ratio R of Zn2+ to OH– (R= nOH–/nZn(II) of the precursor was investigated by varying the amount of NaOH. Samples have been synthesized by the colloidal method at room temperature using (ZnCl2), citric acid (C6H8O9·H2O) and sodium hydroxide (NaOH). The formation of ZnO/C composite was characterized by The X-ray diffraction patterns indicated a high crystallinity and nanocrystalline size of ZnO with hexagonal wurtzite structure. The morphologies of the particles have been studied with a scanning electronic microscopy (SEM). The existence of carbon into the composite was detected by FTIR and EDS. The optical band gap of various ZnO/C composite was calculated from UV-Visible absorption measurement varied in the range 3.301 to 3.282 eV according to R values.